Impact of Intestinal Peptides on the Enteric Nervous System: Novel Approaches to Control Glucose Metabolism and Food Intake - Abot, Anne; Cani, Patrice D.; Knauf, Claude (Frontiers in Endocrinology, 2018)
The gut is one of the most important sources of bioactive peptides in the body. In addition to their direct actions in the brain and/or peripheral tissues, the intestinal peptides can also have an impact on enteric nervous neurons. By modulating the endogenous production of these peptides, one may expect modify the “local” physiology such as glucose absorption, but also could have a “global” action via the gut-brain axis. Due to the various origins of gut peptides (i.e., nutrients, intestinal wall, gut microbiota) and the heterogeneity of enteric neurons population, the potential physiological parameters control by the interaction between the two partners are multiple. In this review, we will exclusively focus on the role of enteric nervous system as a potential target of gut peptides to control glucose metabolism and food intake. Potential therapeutic strategies based on per os administration of gut peptides to treat type 2 diabetes will be described.